P11.22 Radiotherapy effects in GBM Rat model CNS1. (6th September 2019) - Furman, O; Daniels, D; Guez, D; Last, D; Sharabi, S; Talianski, A; Mardor, Y; Zach, L
Abstract: BACKGROUND: CNS1 is a syngeneic glioma model in Lewis Rats. It is an aggressive infiltrating tumor cell line that mimics important aspects of human GBM such as rapid growth, dispersal along blood vessels and white matter, pseudopallisading cells with features of hemorrhage and necrosis. CNS1 tumors are infiltrated with macrophages and T-cells, and were studied in the context of immunotherapy and gene therapy, extracellular matrix and invasion, but CNS1 response to radiation has not yet been described. If we wish to combine novel immune-based therapies with existing GBM protocols that include radiation and chemotherapy, we will need models that respond to these protocols. As a first step in this direction, we sought to describe CNS1 response to radiation in vitro and in vivo. MATERIAL AND METHODS: In vitro, survival of irradiated CNS1 cells was assessed with clonogenic assay. Radiation varied in dose from 0 to 10 Gy and was delivered via Kimtron Polaris X-ray generator. In vivo, male Lewis rats were intra-cranially inoculated with 0.5*10 6 CNS1 tumor cells and monitored for survival. Treated rats (N=6) were subjected to a single 20Gy whole-head radiation treatment under full anesthesia, delivered five days post-inoculation. Control rats (N=5) were anesthetized but not irradiated. Tumor size was monitored using contrast enhanced T1-weighted MRI in both treated and control rats at several time points (4, 6, 11, 18 and 32 days post tumor inoculation). RESULTS: CNS1 cells are sensitive to radiation in vitro, as cell survival decreased after exposure to increasing amounts of radiation. In vivo, while initial tumor size did not significantly differ between groups, rats treated with radiation survived significantly longer than control rats (23.8 ± 5.0 days vs. 11 ± 4.1 days, p<0.005). Growth arrest following irradiation in vivo was not detected 1d after treatment but was observed 6d post-irradiation. Growth arrest was recorded in half of the treated rats, showing no increase in tumor size (N=2) or reduction in tumor volume (N=1) relative to 1d post-irradiation. Tumor growth rates were lower in all irradiated rats relative to control rats. Survival time was negatively correlated with initial tumor size in the control group but not in the treatment group. CONCLUSION: CNS1 rat model of GBM is a valid model of radiotherapy effects on GBM tumors. Further studies combining radiation and chemotherapy are the next step. Support for this work was provided by Israel Cancer Association.